Parent and child perceptions of physical activity with type 1 diabetes. Issue 6 (22nd November 2022) - Giblin, Susan; Scully, Paul; Dalton, Niall; Connolly, Muiriosa; McCaffrey, Alison; Sheikhi, Ali; Neylon, Orla; O'Gorman, Clodagh
Abstract : Introduction: Type 1 diabetes (T1D) is a lifelong illness that affects over 2500 children in Ireland. Management involves complex daily regimens including frequent blood glucose monitoring, pharmacotherapy, dietary management, and physical activity (PA). PA is an important modifiable lifestyle factor. Unfortunately, children with T1D remain physically inactive. Children with T1D face disease-specific barriers and facilitators to PA engagement. All aspects of T1D management for children are supported or supervised by parents. Thus, the purpose of this study was to examine parents' and children's perceptions of barriers and facilitators to PA engagement. Research design and methods: 43 parent and child dyads participated. Parents completed a self-report survey. Children completed a modified version of the Physical Activity Questionnaire for Children (PAQ-C) that explored habitual PA patterns, perceived facilitators and barriers to PA engagement. Results: 21 females, 22 males and their parents (36 mothers, 7 fathers) participated. 69% of males and 90% of females reported that having diabetes did affect their PA participation. 54% of males and 48% of females were insufficiently active based on their total PAQ-C score (<2.9 and <2.7). 53% of parents reported that their children participated in school physical education. 21% of parents reported that their child did not participate in PA outside of the school setting. 23% of parents reported that they did not feel comfortable with their child participating in strenuous PA. A further 30% of parents reported that they only felt comfortable with their child participating in strenuous PA if supervised. 66% of parents reported their child should be more physically active. 83% of parents reported that having T1D did impact their child's PA level. Conclusions: This study demonstrates the potential influence of parents' perceptions on PA engagement in children with T1D. Additional education is needed to support the promotion of PA for children with T1D.